The Effect of Sustainability Report Disclosure and Green Intellectual Capital on Green Firm Value - fitriyani, Desy; Kustinah, Siti (EAJ (Economic and Accounting Journal), 2024)
A company will face ups and downs in company value. In general, companies hope that the value of their company will continue to increase, but in reality, there are still companies that experience a decline. In this case, the main objective of this research is to determine the relationship between sustainability report disclosure and Green Intellectual Capital on Green Firm Value. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The data collection technique used was purposive sampling with a total of 12 companies over the 5 years of research. The data analysis technique used in this research is multiple regression analysis. The results of this research show that Sustainability Report Disclosure has a significant effect on Green Firm Value, while Green Intellectual Capital has no effect on Green Firm Value. Simultaneously Sustainability Report Disclosure and Green Intellectual Capital have a significant effect on Green Firm Value